If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -9 = 8 + x Solving -9 = 8 + x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-1x' to each side of the equation. -9 + -1x = 8 + x + -1x Combine like terms: x + -1x = 0 -9 + -1x = 8 + 0 -9 + -1x = 8 Add '9' to each side of the equation. -9 + 9 + -1x = 8 + 9 Combine like terms: -9 + 9 = 0 0 + -1x = 8 + 9 -1x = 8 + 9 Combine like terms: 8 + 9 = 17 -1x = 17 Divide each side by '-1'. x = -17 Simplifying x = -17
| (x^2)-800x-64=0 | | (8/5x)-(4/5y) | | 3t−18=4(-3-3/4t) | | -.50(4x+6)=-19 | | 8a-3(2a+5)= | | (x+y)(x-y)+(x+y)(y+z)-(x+y)(y-z)= | | 3x+22=25 | | 3ln(4x)=14 | | 6+2n-3=8n+11-5n | | -.25y-1=-19 | | -2x-3/-4=5 | | (D^4+5D^3)y=0 | | 2(X+7)=5x-4 | | 7(5-8)+44=2 | | 3(2n+7)=43 | | 3.87n=6+2.476n | | 3(5t-4)=33 | | 6x-15+18x+6=-12x+32 | | 8a-5=19 | | 0.5lnx+3lnx= | | x^2+12x+36+y^2-4y+4=9 | | 5(x-2)-3=-18 | | 5=2x+33 | | 6(2x+5)=54 | | -3(y+2)+12=21 | | (Y+1)(y-8)=0 | | (6-1i)+(7+3i)= | | 3/7n=27 | | (9x^2)+(63x)+(90)=0 | | 6-4t=3t-22 | | 13=10y-5y-2 | | 36=18/x^(1/2) |